Steel beach eaudiobook - Varley, John (Tantor Media, 2019)
A science fiction epic from "the best writer in America" (Tom Clancy)—Hugo and Nebula award-winning author John Varley. Fleeing Earth after an alien invasion, the human race stands on the threshold of evolution. Their new home is Luna, a moon colony blessed with creature comforts, prolonged lifespans, digital memories, and instant sex changes. But the people of Luna are bored, restless, suicidal—and so is the computer that monitors their existence . . .